HOUSEHOLD FINANCIAL EXPENDITURE PRIORITIES OF RURAL WOMEN IN OSUN STATE, NIGERIA - ALABI , D. L.; SOYEBO , K. O.; OGBIMI , G. E. I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The paper determined the household financial expenditure priorities of rural women in Osun State, Nigeria. A total of 180 women were randomly selected for interview from the three agricultural zones of the State. A Structured interview schedule was used to collect relevant data. Descriptive statistics such as frequency distributions, means and percentages. Appropriate tools were employed to analyse the data collected. Results showed that majority (86.1 %) were between 26 and 55 years of age, majority were married (90%), had no formal education (53.9%), could not estimate their monthly income (53.3%), and majority engaged in multiple occupations. It also revealed that respondents' priorities for provision of good education for the children (mean = 2.87), raising healthy children (mean = 2.86), personal feeding and clothing (mean = 2.67) and freedom from debt (mean = 2.33) were high among women compared with the grand mean of 2.31. Therefore, adequate for women to meet their priorities, adequate schools and health centres should be provided in the rural areas for women to meet their priorities.